ASSESSMENT OF ALLELOPATHIC POTENTIAL OF ARTEMISIA SCOPARIA AGAINST SOME PLANTS - SHALINDER KAUR,; BATISH, DAIZY RANI (The Bioscan, 2010)
A study was conducted to explore allelopathic potential of volatile oil from Artemisia scoparia leaves against Triticum aestivum, Zea mays, Amaranthus viridis, Chenopodium murale and Bidens pilosa. Under laboratory bioassay, seed germination, seedling length, seedling dry weight, chlorophyll content and respiratory activity of different test plants were measured. Different concentrations (0.5, 1.0. 2.5 and 5.0 μL/Petri dish) of Artemisia oil inhibited seed germination of all the test plants. Besides early growth, the chlorophyll content and cellular respiration were also found to be severely affected upon Artemisia oil treatment. In general, the inhibitory effect was greater on weeds than on crops. Among the test plants, A. viridis was observed to be the most sensitive. The study concludes that Artemisia oil possesses stron phytototxicity against weeds and hence could be used as a bioherbicide.